(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the importance of working with object-partitioned spaces in Microsoft Word documents. The problem of mixing rows and creating variants is considered. The advantages and disadvantages of converting the object-participating lines to the variant form using a program compiled in the Delphi programming environment are considered.